Analisis Hubungan Implementasi Zakat Pengurang Pajak Terhadap Perspektif Stakeholder di Banda Aceh - Muhammad Iqbal (Journal of Social and Policy Issues, 2022)
This study aims to measure Analysis of the Relationship between the Implementation of Tax Deduction Zakat to the Perspective of Stakeholders in Banda Aceh, where there are multiple perceptions related to the implementation of tax deduction zakat. In this study, the research method used quantitative descriptive correlation. The data collection techniques used are observation, questionnaire, closing interview. The results of the study of 106 participants using the probability sampling method concluded that there were 5 variable indicators (X2, X3, X4, X5, X6) from the implementation of policies on the application of tax deduction zakat had a high measuring value and on Standards & Targets (X1) with normal values. Meanwhile, the relationship between the analysis of zakat implementation (X) to the perspective of stakeholders (Y) shows insignificant influence. Where every additional 1% in the Implementation variable (X) there is a decrease of 11.7% in the Perspective variable (Y).